Kapasitas Infrastruktur dan Fasilitas pada Kereta Api Angkutan Barang dan Logistik - Abi Prasidi; Muhamad. Rifni (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Very limited capacity of the highway in some economies tract, such as the Trans Java traffic, has an impact on increasing the travel time especially in the use of rail transport, so that a certain pathway requires capacity building and the development of new lines gradually. The purpose of this research was to determine the capacity of rail transport infrastructure that is optimal for the distribution of goods, especially as the company managed by PT. Railway Logistics or KALOG. Another problem is how the government's role and the flow of freight transport demand. In the discussion, through a variety of existing data, the authors use research with phenomenological approach on the basis of qualitative analysis methods interpretative paradigm. Results are expected to be useful for improving knowledge about the needs of rail freight transport on goods distribution on the Java Island. The results of this research will be published in scientific journals. The purpose of this research are two folds. This research combination between qualitative data and quantitative data . The first is to calculate the technology contribution coefficient (TCC) and the second is to determine the priority of technology component development. This research has been done in PT. KALOG, a rail freight transportation company. To calculate the TCC, the author has used the technometric model and the analytical bierarchy process method. By improving these two components, operational problems will be minimized so that operating performance and sales volume will increase. It can then be expected that PT. KALOG will improve its rule in business competition.